2017
DOI: 10.1371/journal.pone.0176355
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of a chicken lung epithelial cell line (CLEC213) reveals a mitochondrial respiratory chain activity boost during influenza virus infection

Abstract: Avian Influenza virus (AIV) is a major concern for the global poultry industry. Since 2012, several countries have reported AIV outbreaks among domestic poultry. These outbreaks had tremendous impact on poultry production and socio-economic repercussion on farmers. In addition, the constant emergence of highly pathogenic AIV also poses a significant risk to human health. In this study, we used a chicken lung epithelial cell line (CLEC213) to gain a better understanding of the molecular consequences of low path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Wang et al 32 had the same finding, where the mRNA levels of CCL19 were upregulated after infection with vvIBDV. Their data suggest that CCL19 acts as a chicken peripheral white blood cells (PWBC) chemotactic factor and facilitates the infiltration of PWBC into the bursa after IBDV infection 33 . Interleukins such as IL17A and IL22 , which were upregulated at 3 dpi, are important to maintain mucosal immunity against virus infection and include induction of antiviral proteins, recruitment of neutrophils to infected areas and enhancement of mucosal barrier repair.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 32 had the same finding, where the mRNA levels of CCL19 were upregulated after infection with vvIBDV. Their data suggest that CCL19 acts as a chicken peripheral white blood cells (PWBC) chemotactic factor and facilitates the infiltration of PWBC into the bursa after IBDV infection 33 . Interleukins such as IL17A and IL22 , which were upregulated at 3 dpi, are important to maintain mucosal immunity against virus infection and include induction of antiviral proteins, recruitment of neutrophils to infected areas and enhancement of mucosal barrier repair.…”
Section: Discussionmentioning
confidence: 99%
“…66 Moreover, transcriptomic analysis of chicken lung epithelial cells infected with a low pathogenic H6N2 strain showed avian influenza virus increased OXPHOS. 67 Induction of energy metabolism proteins, such as ATP synthase and cytochrome b5 type A in the mitochondria, occurs during IAV infection of A549, and inhibition of OXPHOS reduces IAV replication without apparent cellular toxicity. 68,69 Taken together, these in vitro studies indicate that IAV induces changes in glycolysis, the TCA cycle, and OXPHOS in cell lines.…”
Section: In Vitro Studies Of Iav Metabolismmentioning
confidence: 99%
“…It was suggested that activation of cellular metabolism in IAV infections was a compensatory mechanism of the cell for resources (energy, lipid, amino acids and nucleic acids) which were depleted during virion production [ 43 ]. Recently, Meyer et al, 2017 demonstrated increased expression of mitochondrial genes associated with oxidative phosphorylation in LPAI H6N2 and H7N1 viruses in a chicken lung epithelial cell line (CLEC213) [ 44 ]. The same study showed that inhibition of oxidative phosphorylation using oligomycin reduced virus replication without cell toxicity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Meyer et al, 2017 demonstrated increased expression of mitochondrial genes associated with oxidative phosphorylation in LPAI H6N2 and H7N1 viruses in a chicken lung epithelial cell line (CLEC213) [ 44 ]. The same study showed that inhibition of oxidative phosphorylation using oligomycin reduced virus replication without cell toxicity [ 44 ]. Overall, the present data suggested that induction of or maintaining specific metabolic pathways during IAV infections could be important for cell survival and IAV replication.…”
Section: Discussionmentioning
confidence: 99%